Stockholm Fringe Finalist | Excellence in Performance - Korae, Eva (My University, 2026)
AWARD NOMINATION for “ISOLATION” CREATIVE TEAM: ANDRIA MICHAELIDOU, ARIANNA MARCOULIDES & EVA KORAE CATEGORY: EXCELLENCE IN PERFORMANCE
Keywords: Arts and entertainment